Living Donor Liver Transplant for Alcoholic Liver Disease: Data from the Adult-to-adult Living Donor Liver Transplantation Study. Issue 2 (February 2020) - Braun, Hillary J.; Dodge, Jennifer L.; Grab, Joshua D.; Syed, Shareef M.; Roll, Garrett R.; Freise, Chris E.; Roberts, John P.; Ascher, Nancy L.
Abstract : Background: Alcoholic liver disease (ALD) accounts for 15%–30% of transplants performed in the United States and Europe; however, the data on living donor liver transplantation (LDLT) for ALD remain sparse. The purpose of this study was to examine the outcomes following LDLT for ALD using data from the adult-to-adult living donor liver transplantation (A2ALL) study, which represents the largest Western experience with adult-to-adult LDLT. Methods: A retrospective review of A2ALL data collected between 1998 and 2014 was performed. Patients were excluded if they received a deceased donor liver transplant. Demographic data, postoperative outcomes and complications, graft and patient survival, and predictors of graft and patient survival were assessed. Results: Of the 1065 patients who underwent LDLT during the study time period, 168 (15.8%) were transplanted for a diagnosis of ALD. Comparing patients who underwent transplant for ALD with those who were transplanted for other etiologies of liver disease, there was no significant difference in graft survival at 1 (88% versus 84%), 5 (76% versus 74%), or 10 years following transplant (55% versus 61%, P = 0.29). Similarly, there was no difference in patient survival at 1 (94% versus 91%), 5 (83% versus 79%), or 10 years following transplant (61% versus 66%, P = 0.32). Conclusions: LDLT for ALD results in excellent 1-, 5-, and 10-year graft and patient survival. Patients with ALD and impaired renal function have a higher risk of graft loss and death. These findings support the notion that early LDLT for patients with ALD may help optimize outcomes.